2012
DOI: 10.9790/0853-0160507
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxic Periodic Paralysis In A Nigerian: A Case Report

Abstract: Abstarct :Thyrotoxic periodic paralysis is a disorder in which there are episodes of muscle weakness in people with high levels of thyroid hormones. It is a channelopathy characterized by an abnormality in the Na + /K+ ATPase pump due to the effect of excess thyroid hormones which cause an intracellular shift of potassium leading to hypokalaemia in the presence of normal total body potassium 1 . The commonest cause of hyperthyroidism in these patients is Grave's disease 2,3,4 but other causes have also been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is known to occur predominantly among young Asian males, although it has also been reported in American Indians, Mexican Mestizos, Europeans as well as Turkish citizens and amongst others previously mentioned (18)(19)(20). Recent studies from the Indian subcontinent have confirmed the rarity in Indians and there are similarly, few reports from continental Africa (21,22). Male-to-female ratios vary from 17:1 to 20:1 in Japan, 33:1 to 48:1 in the United States of America and 76:1 in Southern China (12,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%
“…It is known to occur predominantly among young Asian males, although it has also been reported in American Indians, Mexican Mestizos, Europeans as well as Turkish citizens and amongst others previously mentioned (18)(19)(20). Recent studies from the Indian subcontinent have confirmed the rarity in Indians and there are similarly, few reports from continental Africa (21,22). Male-to-female ratios vary from 17:1 to 20:1 in Japan, 33:1 to 48:1 in the United States of America and 76:1 in Southern China (12,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%